Housing wealth inequality in urban China: the transition from welfare allocation to market differentiation - Chunling Li; Yiming Fan (The Journal of Chinese Sociology, 2020)
Abstract The differentiation of housing assets is an important embodiment of wealth inequality and is also an important dimension of social stratification. The housing distribution in China has experienced a transition from welfare allocation to market distribution over the decades. This process has led to a change in the housing stratification mechanism and widened housing wealth inequality, which has evoked theoretical disputes about “market transition,” “power persistence,” and “power derivation.” Based on the 2017 Chinese Social Survey (CSS), this article examines the housing wealth inequality in urban China and probes the major drivers of housing stratification. The results suggest that with the progress of housing marketization, market mechanisms have replaced the original socialist redistribution mechanisms and have become the major drivers of housing wealth inequality. However, some of the original socialist institutional arrangements continue to have strong effects on housing wealth inequality. The persisting institutional effect may provide a new perspective for exploring housing wealth inequality in contemporary urban China.